Gravity collapse structures in the Central Precordillera fold-andthrust belt, Argentina - Perucca, Laura; Vargas, Horacio; Rothis, Martin; Tapia, Carla; Esper, Maria Yanina (Journal of Iberian Geology, 2016)
Several landforms found in the fold-and-thrust belt area of Central Precordillera, Pre-Andes of Argentina, which were often associated with tectonic efforts, are in fact related to non-tectonic processes or gravitational superficial structures. These second-order structures, interpreted as gravitational collapse structures, have developed in the western flank of sierras de La Dehesa and Talacasto. These include rock-slides, rock falls, wrinkle folds, slip sheets and flaps, among others; which together constitute a monoclinal fold dipping between 30º and 60º to the west. Gravity collapse structures are parallel to the regional strike of the Sierra de la Dehesa and are placed in Ordovician limestones and dolomites. Their sloping towards the west, the presence of bed planes, fractures and joints; and the lithology (limestone interbedded with incompetent argillaceous banks) would have favored their occurrence. Movement of the detached structures has been controlled by lithology characteristics, as well as by bedding and joints. Detachment and initial transport of gravity collapse structures and rockslides in the western flank of the Sierra de la Dehesa were tightly controlled by three structural elements: 1) sliding surfaces developed on parallel bedded strata when dipping >30° in the slope direction; 2) Joint’s sets constitute lateral and transverse traction cracks which release extensional stresses and 3) Discontinuities fragmenting sliding surfaces. Some other factors that could be characterized as local (lithology, structure and topography) and as regional (high seismic activity and possibly wetter conditions during the postglacial period) were determining in favoring the steady loss of the western mountain side in the easternmost foothills of Central Precordillera.